The effect of long-term planting of poplar trees on the morphology and yield of neighboring summer maize on cropland in humid and semi humid regions of China - Zhong, Mingxing; Li, Xiuge; Li, Jingxian; Tang, Jiahui; Zhao, Zihao; Cao, Boning (Frontiers in Agronomy, 2025)
Rapid urbanization has led to a large-scale loss of cropland to non-agricultural uses. To avoid losses caused by abandonment, farmers working in cities have converted part of their farmland into economic forests (Primarily poplar). To assess how converting cropland to forest land negatively impacts neighboring grain production, we selected five agroforestry interfaces in humid and semi-humid regions of China. We investigated the effects of long-term poplar planting on the production process of summer maize in neighboring fields. Eight sampling points (d1-d8) were established at 1-meter intervals along the agroforestry interface extending into the maize field, at each interface. During the maize maturity stage, morphological structure, yield, and dry matter distribution were measured. The results showed that long-term planting of poplar trees had a significant effect on the growth and harvest parameters of neighboring summer maize. Compared to the farthest distance (control), the maize plants closest to the poplar trees exhibited reductions in plant height, stem diameter, and leaf area by 46.4%, 34.9%, and 60.2%, respectively. Compared to control, root, stem, leaf, tassel, bract, and corncob dry weight at d1 were reduced by 47.2%, 28.7%, 42.6%, 27.5%, 35.3%, and 40.5%, respectively, and the yield per spike and total dry weight at d1 were reduced by 94.9% and 58.0%, respectively. Furthermore, trend analysis revealed that these parameters exhibited logarithmic growth trends with increasing distance (All R2 > 0.80). Structural equation modeling demonstrated that summer maize morphological structure and dry matter distribution directly and indirectly influenced yield per spike and total dry weight through distinct pathways. These findings provide management implications for mitigating the negative impacts of agroforestry systems on agricultural production in humid regions, while also providing a parameter basis for accurately assessing the grain yield reduction effect resulting from the large-scale conversion of agricultural land to forestry.